Paper Town: The Social Production of Territory in the Industrial Town of Atenquique, Mexico - Alejandro Ponce de León Pagaza (Íconos)
This article analyzes the social production of space in Atenquique, an industrial town in the southern region of Jalisco in western Mexico. The theoretical framework draws on insights from critical geography. Through the case of Atenquique we reflect on the transformation of the area from the beginning of the neoliberal period in Mexico. Neoliberalism ushered in the growth of precarious and insecure working conditions, something which has deepened over the past several decades. The methodology employed is based on ethnographic research undertaken over a period of four months in Atenquique. During this time period we used three different audiovisual methods to collect information: photography, oral history and the production of an ethnographic documentary film. The results of the study show how the ex-inhabitants of Atenquique have knit together complex constructions- both material and symbolic- that provide insight on how the changes of the past several decades have affected the area. In the conclusions, we return to the broader debates on the local and territorial consequences of the implementation of the neoliberal policies in Mexico.